Differences between Soil Ammonium and Nitrate Spatial Pattern in Six Plant Communities. Simulated Effect on Plant Populations (Plant and Soil, 2005)
Geostatistical descriptions of soil heterogeneity patterns for plant communities are abundant in literature, however there is no information on the consequences of diﬀerent soil spatial patterns on resource availability for plant populations. Conditional simulations on the spatial distribution of soil NH4–N and NO3–N were carried out in order to study the eﬀect of contrasted patch sizes on nitrogen availability for individuals with increasing root system size. The semivariogram range (an indication of patch size) for soil NH4–N and NO3–N in six plant communities was found to be very variable, and was higher for soil NH4– N than for soil NO3–N in each community. A positive correlation was observed between organic matter and NH4–N spatial ranges in the six plant communities, but not between NO3–N and NH4–N. Probabilities of ﬁnding a high soil N concentration within simulated plant populations depended on N patch size and root system size. Thus, a population taking up NH4 –N (higher spatial range values) would be more heterogeneous (i.e. Individuals will have diﬀering probabilities of ﬁnding a high soil N concentration) than the same population taking up NO3–N. Likewise, a seedling population taking up NH4–N or NO3–N would be more heterogeneous than a large tree population in the same area, where individuals would have similar probability of ﬁnding a high soil N concentration. These results showed that the spatial patch size of limiting resources has important consequences at the population level, since it determines the probability of ﬁnding a favourable site and therefore diﬀering performances of individuals within a population.

Differences between Soil Ammonium and Nitrate Spatial Pattern in Six Plant Communities. Simulated Effect on Plant Populations - Gallardo, Antonio; Paramá, Rocio; Covelo, Felisa (Plant and Soil, 2005)
Geostatistical descriptions of soil heterogeneity patterns for plant communities are abundant in literature, however there is no information on the consequences of diﬀerent soil spatial patterns on resource availability for plant populations. Conditional simulations on the spatial distribution of soil NH4–N and NO3–N were carried out in order to study the eﬀect of contrasted patch sizes on nitrogen availability for individuals with increasing root system size. The semivariogram range (an indication of patch size) for soil NH4–N and NO3–N in six plant communities was found to be very variable, and was higher for soil NH4– N than for soil NO3–N in each community. A positive correlation was observed between organic matter and NH4–N spatial ranges in the six plant communities, but not between NO3–N and NH4–N. Probabilities of ﬁnding a high soil N concentration within simulated plant populations depended on N patch size and root system size. Thus, a population taking up NH4 –N (higher spatial range values) would be more heterogeneous (i.e. Individuals will have diﬀering probabilities of ﬁnding a high soil N concentration) than the same population taking up NO3–N. Likewise, a seedling population taking up NH4–N or NO3–N would be more heterogeneous than a large tree population in the same area, where individuals would have similar probability of ﬁnding a high soil N concentration. These results showed that the spatial patch size of limiting resources has important consequences at the population level, since it determines the probability of ﬁnding a favourable site and therefore diﬀering performances of individuals within a population.
Keywords: geostatistics; plant populations; root system size; Soil; soil ammonium; soil heterogeneity; Soil nitrate